(untitled) (Revista História & Perspectivas, 2009)
Este trabalho enfoca um grupo de quatro localidades espalhadas por toda a antiga província de Goiás. O levantamento das suas populações, realizado em princípios do século XIX, produziu listas contendo nome, idade, cor e estado conjugal da população livre e a condição social de toda a população, dividida segundo o domicílio. Procuro caracterizar a sua população e analisar seus domicílios, percebendo em que medida o sexo de seus chefes influenciaram seu perfil. PALAVRAS-CHAVE: gênero, demografia histórica, Brasil. ABSTRACT This work focuses on a group of people from four little villages in the old Province of Goiás. The survey made in the beginning of the 15th century listed name, age, skin color, marital status (of free population) and social condition of all population according to the domicile. I seek to characterize this population and analyze his household in order to grasp in which measure the sex of the householders influenced his profile. KEYWORDS: gender, historical demography, Brazil.